Modal Sosial Paguyuban Pedagang Kaki Lima (Studi Etnografi Paguyuban PKL Mekar Sore Jalan Hos Cokroaminoto Kabupaten Ponorogo) - Ana Rita Dahnia; Anis Wahda Fadilla Adsana; Zulfatuz Zakiyah (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This study aims to determine the social capital of the association of street vendors in the scope of economics and development. The research method used is a qualitative method to obtain the data that researchers need and to understand the subject in depth. Researchers used an ethnographic approach that focused on a group that had the same goal, the group studied in this study was the Mekar Sore street vendor association. The research location is on Jalan Hos Cokroaminoto, Ponorogo Regency. Data collection techniques in this study were to gather information through observation, interviews and documentation. The results of this study indicate the social capital of the role of the Mekar Sore street vendor association with its influence on the economy and development on Jalan Hos Cokroaminoto. Jalan Hos Cokroaminoto which has undergone a face off is similar to Malioboro Yogyakarta with the aim as a city tourism sector there is a role from various stakeholders in its development, one of which is the Mekar Sore street vendor association. The association is a well-structured group, as evidenced by the existence of a management structure and routine activities for the sustainability of their economy and efforts to protect the environment on Jalan Hos Cokroaminoto. In addition, with social capital, the association is trying to change the image of street vendors who care about environmental issues.